Improving the Legal Provisions on Initiating Cases at Victim’s Request: Recommendations from the Criminal Procedure Laws of Russia and China - Son, Mai Thanh; Dung, Bui Thu (VNU Journal of Science: Legal Studies, 2024)
Initiating criminal cases at the victim's request is a relatively special provision in Vietnamese criminal procedure, adopted to protect and enhance the victim's rights. However, this provision in the Criminal Procedure Code 2015 still contains some unreasonable points. Meanwhile, Russia and China - two countries with significant similarities and influences on Vietnam's legislative process - have advanced provisions to enhance the victim's position in the criminal procedure law, particularly from the stage of initiating criminal proceedings.  The article utilizes synthetic, analytical, and comparative methods to analyze the legal provisions surrounding the initiation of criminal proceedings at the victim's request in Vietnam and the two countries above. Based on this, the article proposes amendments to Article 155 of the Criminal Procedure Code 2015 and several recommendations to improve the victim's position while protecting their legal rights and interests when participating in criminal proceedings.